2009
DOI: 10.3748/wjg.15.1153
|View full text |Cite
|
Sign up to set email alerts
|

Islet transplantation and antioxidant management: A comprehensive review

Abstract: Islet transplantation as a promising treatment for type 1 diabetes has received widespread attention. Oxidative stress plays an essential role in cell injury during islet isolation and transplantation procedures. Antioxidants have been used in various studies to improve islet transplantation procedures. The present study reviews the role of oxidative stress and the benefits of antioxidants in islet transplantation procedures. The bibliographical databases Pubmed and Scopus were searched up to November 2008.All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(43 citation statements)
references
References 69 publications
0
42
0
Order By: Relevance
“…In this area of research, previous studies have shown that metal oxide NPs, including CeO 2 , Y 2 O 3 , ZnO, and MgO, were capable of enhancing cell survival and function under conditions of oxidative stress; [33][34][35][36][37] the reason for increasing insulin by metal oxide NPs was justified by their antioxidant property. 38 In addition, it was demonstrated that using metal oxide NPs induces a cascade of protein phosphorylation due to increase of ATP/ADP ratio that finally leads to secretion of insulin.…”
mentioning
confidence: 99%
“…In this area of research, previous studies have shown that metal oxide NPs, including CeO 2 , Y 2 O 3 , ZnO, and MgO, were capable of enhancing cell survival and function under conditions of oxidative stress; [33][34][35][36][37] the reason for increasing insulin by metal oxide NPs was justified by their antioxidant property. 38 In addition, it was demonstrated that using metal oxide NPs induces a cascade of protein phosphorylation due to increase of ATP/ADP ratio that finally leads to secretion of insulin.…”
mentioning
confidence: 99%
“…Good evidence indicates that cyclic nucleotides are able to act against oxidative stress [49,50] that may explain anti-toxic stress potential of silymarin in the present model of T1DM. Regarding existing literature, silymarin has enough potential to be tested for improvement of pancreatic islet transplantation procedures [51].…”
Section: Discussionmentioning
confidence: 99%
“…It has been illustrated that NF-κB is responsible for over-expression of innate immune mediators [3]. Activation of NF-κB causes destruction and dysfunction of IPβCs [4]. Moreover, glucose itself promotes proinflammatory cytokines and inflammatory matrix metalloproteinase (MMP)-2.…”
Section: Introductionmentioning
confidence: 99%
“…A number of evidence on the relationship between oxidative stress and diabetes (32)(33)(34)(42)(43)(44)(45)(46)(47) even by OP compounds (48) supports this conclusion, and calls for further research of the benefi cial effects of antioxidants (49). Our future work will focus on the balance between insulin secretion, antioxidant levels, and islet cytotoxicity.…”
Section: Figure 6 Insulin Release From Islets Of Langerhans Incubatedmentioning
confidence: 99%